Improved Hepatic Differentiation Strategies for Human Induced Pluripotent Stem Cells - Sgodda, M.; Mobus, S.; Hoepfner, J.; Sharma, A.D.; Schambach, A.; Greber, B.; Ott, M.; Cantz, T. (Current Molecular Medicine, 2013)
Based on their almost unlimited self-renewal capacity and their ability to differentiate into derivatives of all three germ layers, human induced pluripotent stem cells (hiPSCs) might serve as a preferable source for hepatic transplants in metabolic liver disorders or acute liver failure. Furthermore, the generation of patientspecific hiPSCs might facilitate the development of innovative therapeutic strategies by accurately modelling disease in vitro. In our study, we aimed for an efficient hepatic differentiation protocol that is applicable for both human embryonic stem cells (hESCs) and hiPSCs. We attempted to accomplish this goal by using a cytokine and small molecule-based protocol for direct differentiation of hESCs and hiPSCs into hepatic cells. Selecting differentiated hepatic cells was possible using an albumin promoter-driven G418 resistance system. Due to IRES-dependent dTomato reporter expression, we were able to track hepatic differentiated cells and we evaluated the most efficient time frame for G418 selection. The status of hepatic differentiation was determined by qRT-PCR comparing the expression of hepatic markers such as AFP, ALB, SOX17, and HNF4 to standard hepatic cells. Functional analysis of the hepatic phenotype was obtained by measuring secreted albumin levels and by analysis of cytochrome P450 type 1A1 activity (EROD). The percentage of differentiated cells was quantified by FACS analysis. In conclusion, our improved protocol demonstrates that both pluripotent cell sources (hESC and hiPSC) can efficiently be differentiated into mature hepatic cells with functional characteristics similar to those of standard hepatic cell lines such as HepG2.
Keywords: Hepatic differentiation